Horacio (Oda 2, 16) en Francisco de Medrano (Oda XXIV) - Mañas Núñez, Manuel (1995)
Horacio es utilizado continuamente como fuente en el cancionero de Francisco de Medrano. Estudiamos la presencia del poeta latino (Flor, carm. 2,16) en Medrano (oda XXIV) y analizamos la recreación.
Horace’s works are systematically used as source in the poetie colleetion of the Spanish poet Francisco de Medrano. The presence of this Latin poet (Hor., carm. 2,16) in Medrano (ode XXIV) has been studied in this essay, and the imitative process has been analysed.
Keywords: Horacio Flaco, Quinto; Medrano, Francisco de